The Effect of Student Teams Achievement Division (STAD) Model on Learning Outcomes in Class X Economics Lessons at SMA Negeri 1 Kirange Academic Year 2022/2023 - Rouli Milenia Qwint Siboro; Putri Kemala Dewi Lubis (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the improvement in class economics learning outcomes using the Student Teams Achievement Division (STAD) learning model for class X students at SMA Negeri 1 Kisaran. The research method used in this research is the experimental method. The population in this study were all class X students at SMA Negeri 1 Kisaran, totaling 360 students, in 10 classes. The sampling technique uses purposive sampling, namely a sampling technique according to certain considerations, so that the sample is 72 students. In this study, the sample students were categorized into 2 groups. By testing the hypothesis using the paired t-test, the results obtained were sig.2 tailed at 0.000 < 0.05 using the Student Teams Achievement Division (STAD) learning model in improving students' economic learning outcomes.